Tunable true-time delay unit based on opto-VLSI processing - Feng, X.; Juswardy, Budi; Alameh, K. (2008)
A novel tunable true-time delay unit is proposed and demonstrated. The unit is based on the use of an Opto-VLSI processor that dynamically selects a single waveband or multiple wavebands from an RF-modulated broadband optical signal and routes them to a high-dispersion fiber for arbitrary time delay synthesis. Experimental results demonstrate continuously tunable time delay of up to 4 ns.